Moral and religion in Salesian schools. Experiences of children and young people in Comodoro Rivadavia (Argentina) in the 60’s - Lago, Luciana (Sociedad y religión, 2021)
The work focuses on the study of two Salesian educational experiences oriented to the childhood and youth of Comodoro Rivadavia in the 1960s. A situated analysis is proposed that seeks to investigate the connections between the social and economic oil matrix and Salesian formation. The axis of the inquiry focuses on understanding the educational profiles, strategies, practices of evangelization and assistance that the Salesians deployed for the moral formation of children and young people from different social sectors. In a relational way, the experiences of children and young people linked to these projects are recovered to understand the ways in which they participated, recognizing their agency capacity. The research is based on a qualitative methodology based on interviews, press records and documentary sources. Religious experiences and practices are analyzed to show the different orientations on childhoods and the youth of Comodoro. The conclusions of the work show that, with adaptations, the Salesian discourse survives regarding its civilizing, nationalizing actions and that it brings progress to the Patagonian territory. Children and youth are seen in a differential way, while for the middle sectors their professional training weighs for the popular sectors the key is their instruction and moralization.